2009
DOI: 10.1614/ws-08-152.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of 98140 Corn With Gat4621 and hra Transgenes to Glyphosate and ALS-Inhibiting Herbicides

Abstract: The transgenic corn line 98140 has a high level of resistance to glyphosate and all five chemical classes of herbicides that inhibit acetolactate synthase (ALS). The dual herbicide resistance is due to a molecular stack of two constitutively expressed genes: gat4621, which produces a glyphosate acetyltransferase that rapidly inactivates glyphosate, and hra, which produces a highly resistant ALS. On a rate basis, the positive 98140 isoline with a single copy of the gat4621 gene is over 1,000-fold more resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…Agrobacterium with different T-DNAs in the binary plasmid are referred to as "strains." Two selectable markers were used in experiments: a sulfonylurea herbicide resistance marker 'Hra' (Green et al 2009), driven by the sorghum ALS promoter (see Supplemental Table S-2), was used for selection with 0.1 mg L −1 imazapyr in both the maturation and rooting medium, or the Ubi pro ::NPTII gene was used with 150 mg L −1 G418 in both the maturation and rooting medium (13329 and 13158 media, respectively). Constructs used in this study are shown in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Agrobacterium with different T-DNAs in the binary plasmid are referred to as "strains." Two selectable markers were used in experiments: a sulfonylurea herbicide resistance marker 'Hra' (Green et al 2009), driven by the sorghum ALS promoter (see Supplemental Table S-2), was used for selection with 0.1 mg L −1 imazapyr in both the maturation and rooting medium, or the Ubi pro ::NPTII gene was used with 150 mg L −1 G418 in both the maturation and rooting medium (13329 and 13158 media, respectively). Constructs used in this study are shown in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…The conditions for Agrobacterium suspension culture preparation following embryo isolation and infection have been previously described ( Lowe et al., 2018 ; Hoerster et al., 2020 ). Two selectable markers were used in experiments: HRA ( Green et al., 2009 ), a sulfonylurea herbicide resistance marker, driven by the sorghum Als promoter for selection with 0.1 mg/L imazapyr in culture medium, or the Ubi pro : NPTII gene for selection with 150 mg/L G418 in culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…For new GM soybean, 2,4-D and dicamba resistance traits will always be used in stacks with at least one other herbicide-resistant trait. Glyphosate and ALS trait stack, recently deregulated in the US, possibly will allow the use of ALS-inhibiting herbicides with soil residual that are too phytotoxic to use on conventional crop cultivars [24]. In reference [25], diversification may make weed management more complex, but growers must not use new GM crop resistant to herbicides in the same way that some used initial GM crops, in order to rely only on one herbicide until it is no longer effective and then switch herbicides.…”
Section: Issues On Weed Managementmentioning
confidence: 99%